An Event-Related Potentials Study on the Syntactic Transfer Effect of Late Language Learners - Deng, Taiping; Deng, Dongping; Feng, Qing (Frontiers in Psychology, 2022)
The present study tried to explore the syntactic transfer effect of the non-local subject-verb agreement structure with plural head noun after two intensive phases of input training with the event-related potentials (ERP). Syntactic transfer effect in language field means the use of the previously entrenched syntactic representation or acquired knowledge during the training phases in dealing with new situations. The non-local subject-verb agreement stimuli with the plural head nouns, which never appeared in training phases, were used for the stimuli. 26 late L1-Chinese L2-English learners, who began to learn English after a critical period and participated our previous experiments, were asked back to take part in this syntactic transfer experiment. Results indicated that a significant ERP component P600 occurred in the key region (the verb) of the sentences with syntactic violations in the experimental group, but none in the control group. This demonstrated that there was a significant transfer effect of the input training. The possible theoretical explanation was provided and also the mellability of the late L2 learners was discussed.